(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Change and development of phraseological meaning is not merely a feature of illustrations in a literary discourse, as we have seen from Thurber and from Lewis Carroll’s Alice’s Adventures in Wonderland (a sustained visual pun). Instantial stylistic use is a mode of figuration that is also common to various types of newspaper texts, which easily combine verbal and visual representation in creative thinking